Comparative Analysis of the Environmental Load of Natural Refrigerant (R290) - Bouzghiba, Houria; Géczi, Gábor (Journal of Central European Green Innovation, 2022)
Due to the detrimental environmental consequences of synthetic refrigerants, natural refrigerants have gained renewed interest as alternative refrigerants for a variety of applications due to their minimal ozone depletion potential (ODP) and insignificant global warming potential (GWP). This study compares the performance characteristics of R32-based Air Source Heat Pump (ASHP) to those of R290 and R410A refrigerants. In this study, analyses of the cooling effect, heat output, compressor work input, and coefficient of performance (COP) for various refrigerants will be undertaken. Additionally, the environmental consequences of R32, R410A, and R290 are discussed. The results indicate that R290 is the most efficient refrigerant in terms of performance coefficient, followed by R410A and R32. Considering environmental protection aspects, R290 is a favorable substitute medium.